Sea stars of the genus Henricia Gray, 1840 (Echinodermata, Asteroidea) from Vostok Bay, Sea of Japan - Chichvarkhin, Anton; Chichvarkhina, Olga; Wakita, Daiki (PeerJ, 2019)
We report seven species of the genus Henricia Gray, 1840 that were found in Vostok Bay, and two species from adjacent area, known from museum collection or seen in underwater footage. while existing literature reported no confirmed species from this area. Most of these species: H. djakonovi, H. alexeyi, H. densispina, H. hayashii, H. granulifera, H. pacifica, H. asiatica, and H. oculata robusta were reported from the Sea of Japan previously. H. nipponica, known from Japan, is reported from Russian seas for the first time. All studied taxa are re-described here using a range of morphological characters and partial 16S rRNA nucleotide sequences, life colorations of several species are reported for the first time, and an identification key is provided. Lectotype designations are fixed for studied series of species described by AM Djakonov.
Keywords: Echinasteridae; Local fauna; Western Pacific